THREE NOVELS BY MAREK TOMAN - Gilk, Erik (Bohemica Olomucensia, 2020)
The paper focuses on three novels by Marek Toman (*1967) published during three years: Chvala oportunismu (2016), Neptunova jeskyne (2018) and Oko zraloka (2018). Although Toman's novels use different narrative methods, they have got common features. They process Czech modern history by artificial means and concentrate on the most important turning points of Czech history in the 20th century. The first named fiction is very inventive for its narrator that is building of Czernin Palace, seat of the Czech Ministery of Foreign Affairs. But next works put a more conventional view of the Czech history and have not got such elaborated composition.
Keywords: Czech literature after 1989; Czech fiction; modern Czech history; Marek Toman